(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In The Internet, A Number Of Services Have Become Flexible And Cost-Effective Because Of Cloud Computing. Security Is The Major Hitch In Cloud Computing And Many Researchers Have Studied And Discussed The Problems Relating To This Issue. Various Techniques Are Requiring Ensuring The Integrity Of Data Which Is The Integral Part Of Cloud Storage Adoption. Five Different Trust Attributes Are Collected From Third Party And Its Trust Model In This Work And Integrity Of Data Are Assured Through The Servers. Ant Lion Optimizer (Alo) Algorithm Uses Optimal Scheduling, Which Is Proposed And Contrasted With Particle Swarm Optimization (Pso).